Estudo sobre o uso do Picture Archiving and Communication System (PACS) em um Hospital Universitário da cidade de Belo Horizonte, Minas Gerais, Brasil - Adriana Maria Lamego Rezende (2023)
A study on the use of the Picture Archiving and Communication System (PACS) at the Hospital the Federal University of Belo Horizonte city of Minas Gerais (HC-UFMG). 2023. Dissertation (Professional Master's in Work and Participatory Management in Health) - School of Nursing, Federal University of Minas Gerais, Belo Horizonte, MG, Brazil. In the hospital context, imaging tests are essential to support and qualify clinical decision- making. Radiology, as a specialty of medicine, aims to assist referring physicians in making diagnostic decisions. Radiology is essential because in several situations, treatment is derived from it. In the context of Hospital das Clínicas of the Federal University of Minas Gerais (HC- UFMG), we used the Picture Archiving and Communication System (PACS) for archiving and communication medical images. Which is used in the radiology sector and allows other requesting professionals to access and analyze medical images efficiently and securely. A question that guided this study was: What are the potentialities and challenges resulting from the use of the future Archiving and Communication System (PACS) in the Radiology sector Clinical Hospital of Federal University of Minas Gerais (HC-UFMG)? The purpose of the research was to analyze the potentialities and challenges resulting from the use of PACS in the radiology at HC-UFMG. This is qualitative, exploratory and descriptive. The research scenario was the Radiology sector of HC-UFMG. The participants were nine radiologists from that sector. The following inclusion criteria were adopted: effective radiologists (doctors who were on public service and who were not on vacation and/or away) who used the PACS system in the Radiology sector of HC-UFMG. As exclusion criteria it was adopted: physicians who did not make up the effective physicians in the sector, that is, who were volunteers or residents; were excluded also two doctors who were on vacation and two who were on formal leave during the period of data collection. Data collection was carried out through interviews with a script semi-structured and documentary survey. Data analysis of the interviews was carried out by the Content Analysis technique and documents by document analysis. The research was submitted to the Research Ethics Committee of the Federal University of Minas Gerais (COEP/UFMG) and approved by CAAE 67471123.0.0000.5149, after approval by Department of Health Management and approval of the Teaching and Research Management (GEP) of the HC-UFMG The main results indicate that the PACS is considered a tool central and efficient by the radiologist interviewed, as it facilitates access and visualization of imaging exams, streamline clinical decision-making and contribute to more coordinated and effective. It is concluded that the relevance of this study is reflected in the contribution to the understanding of the potentialities and challenges related to the use of PACS in a hospital university, providing subsidies to improve health management and assistance to patients. The technical product of this study is a technical report, to be presented to the management from HC-UFMG. Keywords: Picture Archiving and Communication System (PACS). Technology. Efficiency. Health management.